Gαi2+ vomeronasal neurons govern the initial outcome of an acute social competition - Pallé, Anna (2020)
Pheromone detection by the vomeronasal organ (VNO) mediates important social behaviors across different species, including aggression and sexual behavior. However, the relationship between vomeronasal function and social hierarchy has not been analyzed reliably. We evaluated the role of pheromone detection by receptors expressed in the apical layer of the VNO such as vomeronasal type 1 receptors (V1R) in dominance behavior by using a conditional knockout mouse for G protein subunit Gαi2, which is essential for V1R signaling. We used the tube test as a model to analyze the within-a-cage hierarchy in male mice, but also as a paradigm of novel territorial competition in animals from different cages. In absence of prior social experience, Gαi2 deletion promotes winning a novel social competition with an unfamiliar control mouse but had no effect on an established hierarchy in cages with mixed genotypes, both Gαi2−/− and controls. To further dissect social behavior of Gαi2−/− mice, we performed a 3-chamber sociability assay and found that mutants had a slightly altered social investigation. Finally, gene expression analysis in the medial prefrontal cortex (mPFC) for a subset of genes previously linked to social status revealed no differences between group-housed Gαi2−/− and controls. Our results reveal a direct influence of pheromone detection on territorial dominance, indicating that olfactory communication involving apical VNO receptors like V1R is important for the outcome of an initial social competition between two unfamiliar male mice, whereas final social status acquired within a cage remains unaffected. These results support the idea that previous social context is relevant for the development of social hierarchy of a group. Overall, our data identify two context-dependent forms of dominance, acute and chronic, and that pheromone signaling through V1R receptors is involved in the first stages of a social competition but in the long term is not predictive for high social ranks on a hierarchy.